Interaction between the Rous sarcoma virus transforming protein and two cellular phosphoproteins: analysis of the turnover and distribution of this complex. - Brugge, J (1983)
The transforming protein of Rous sarcoma virus (RSV), pp60src, was previously shown to associate with two cellular proteins of Mr 90,000 and 50,000 in RSV-transformed chicken cells. In this report, we demonstrate that this interaction is specific for a discrete population of pp60src molecules. Newly synthesized pp60src was found to preferentially associate with pp90 and pp50 to form a short-lived complex. The half-life of this complex varied from 9 to 15 min in cells transformed by nondefective strains of RSV. This interaction between pp60src, pp50, and pp90 took place in a soluble fraction of the cell, and the complex-bound pp60src molecules were not phosphorylated on tyrosine. These results suggest that pp90 and pp50 may be involved in the processing of pp60src molecules before the association of pp60src with the plasma membrane. The kinetics of dissociation of this complex were shown to be altered in cells infected with viruses containing a temperature-sensitive defect in the src gene. When cells infected with these viruses were grown at the nonpermissive temperature, more than 90% of the pp60src molecules were associated with pp90 and pp50, and little or no dissociation was observed in a 3-h chase period. These results suggest that mutations in the src gene which affect the transforming activity of pp60src also affect the stability of the interaction of pp60src with pp90 and pp50.